Splitting Votes, Splitting Hairs? Rationale for Split-Ticket Voting at the Federal, Regional, and European Elections of May 2014 in Belgium. Issue 4 (24th May 2018) - Willocq, Simon; Kelbel, Camille
Abstract: This article investigates the determinants of split-ticket voting at the 2014 simultaneous federal, regional, and European elections in Belgium. We seek to explain why over a third of the voters made distinct party choices at different levels of government. Using data from the 2014 PartiRep Survey, we test a model of ballot-splitting, incorporating various types of explanations. Of specific interest to students of federalism, results show that some voters engage in vertical party-balancing. At the same time, perceiving a differential in importance between the levels does not appear as a driver of split-ticket voting, which runs contrary to the main assumption of the "second-order" elections model.